Evaluation of Association Studies and an Updated Meta-Analysis of VDR Polymorphisms in Osteoporotic Fracture Risk - Mu, Yi-yang; Liu, Biao; Chen, Bin; Zhu, Wang-fa; Ye, Xiang-Hua; Li, Hong-zhuo; He, Xiao-feng (Frontiers in Genetics, 2022)
Background: Several studies have examined the association between vitamin D receptor (VDR) polymorphisms and osteoporotic fracture risk; however, the results are not uniform. Furthermore, many new articles have been published and; therefore, an updated meta-analysis was performed to further explore these issues. Objectives: To investigate the association between VDR, BsmI, ApaI, TaqI, FokI, and Cdx2 polymorphisms and osteoporotic fracture risk. 1 Methods: The odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the association between VDR BsmI, ApaI, TaqI, FokI, and Cdx2 polymorphisms, and the risk of osteoporotic fracture. We also used the false positive reporting probability (FPRP) test and the Venice criteria to evaluate the credibility of the statistically significant associations. Results: Overall, this study found that the VDR ApaI and BsmI polymorphisms significantly increased the risk of osteoporotic fracture in European countries and America, respectively. However, when we performed sensitivity analysis after excluding low quality and Hardy-Weinberg Disequilibrium (HWD) studies, we found that only individuals with the double-mutated genotype have an increased risk of osteoporotic fracture in European countries. In addition, when we assessed the credibility of the positive results, we found that the positive results were not credible. Conclusion: This meta-analysis indicates that there may be no significant association among the polymorphisms of VDR BsmI, ApaI, TaqI, FokI, and Cdx2 and the risk of osteoporotic fracture. The increased risk of osteoporotic fracture is most likely due to false positive results.